The effect of atmospheric ducts on the propagation of AIS signals. Issue 2 (3rd April 2019) - Tang, Wenlong; Cha, Hao; Wei, Min; Tian, Bin
ABSTRACT: Electromagnetic wave propagates abnormally under atmospheric duct conditions. It is very important to study the influence of atmospheric duct on the radio propagation of the shipborne automatic identification system (AIS). AIS is a maritime navigation safety communication system that operates in the very high frequency (VHF) maritime mobile band and was developed primarily for collision avoidance. When AIS signals propagating in the atmospheric duct, the trapping effect can extend the signal range beyond the line-of-sight. In this work, the transmission of AIS signals under atmospheric duct conditions is modelled using the parabolic equation method. The simulation results demonstrate that both standard surface duct and surface-based duct can extend the detection range of AIS, whereas surface-based duct shows higher trapping capabilities over the standard surface duct. The results can be implemented to improve maritime situation awareness.